2017
DOI: 10.1044/2017_jslhr-h-17-0119
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Vocabulary, Cognitive Flexibility, and Inhibitory Control Differentially Predict Older and Younger Adults' Success Perceiving Speech by Talkers With Dysarthria

Abstract: Although older and younger adults had equivalent performance identifying words produced by talkers with dysarthria, older adults appear to utilize more cognitive support to identify those words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…We previously found that older adults were poorer than younger adults at perceiving foreign-accented speech [3], but that there was no difference between older and younger adults when perceiving dysarthric speech [4]. The current results expand on our previous findings by suggesting that even though older adults' performance may differ across speech types, common speech perception mechanisms may be at play.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We previously found that older adults were poorer than younger adults at perceiving foreign-accented speech [3], but that there was no difference between older and younger adults when perceiving dysarthric speech [4]. The current results expand on our previous findings by suggesting that even though older adults' performance may differ across speech types, common speech perception mechanisms may be at play.…”
Section: Discussionsupporting
confidence: 68%
“…Our previous reports [3,4] indicated that older adults' perception of both accented and dysarthric speech was predicted by working memory capacity and by interactions between hearing acuity and inhibitory control. An interaction between hearing acuity and cognitive flexibility was only found for accented speech [3] whereas a main effect of cognitive flexibility and an interaction between hearing acuity and receptive vocabulary were only found in our investigation of dysarthric speech [4].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…where ϵ i (t) are error terms explaining the additional variations inπ i t ð Þ, from the smooth linear curves π i (t). Such practices are common in the current literature (Holt et al, 2018;Ingvalson et al, 2017;Moyle et al, 2007;Reetzke et al, 2018). Figure 3 shows the population-level estimate, fitting the above model to the sound-to-category data using the lme4 package in R.…”
Section: Linear Probability Modelsmentioning
confidence: 99%